2018
DOI: 10.1371/journal.ppat.1006851
|View full text |Cite|
|
Sign up to set email alerts
|

Phospholipid scramblase 1 interacts with influenza A virus NP, impairing its nuclear import and thereby suppressing virus replication

Abstract: Transcription and replication of the influenza A virus (IAV) genome occur in the nucleus of infected cells and are carried out by the viral ribonucleoprotein complex (vRNP). As a major component of the vRNP complex, the viral nucleoprotein (NP) mediates the nuclear import of the vRNP complex via its nuclear localization signals (NLSs). Clearly, an effective way for the host to antagonize IAV infection would be by targeting vRNP nuclear import. Here, we identified phospholipid scramblase 1 (PLSCR1) as a binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 53 publications
(79 reference statements)
2
72
0
Order By: Relevance
“…Previous study has shown that druginduced NP aggregation in cytosol might block migration of NP into nucleus and subsequently impair virus replication (Kao et al, 2010). Host protein phospholipid scramblase 1 (PLSCR1) (Luo et al, 2018) and moloney leukemia virus 10 (MOV10) (Zhang et al, 2016) also have been reported can interact with importin α to inhibit viral vRNP imported into nucleus. Therefore, aggregation of NP in mPSCs Oct4+ might block vRNP nuclear import, then interfere with vRNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that druginduced NP aggregation in cytosol might block migration of NP into nucleus and subsequently impair virus replication (Kao et al, 2010). Host protein phospholipid scramblase 1 (PLSCR1) (Luo et al, 2018) and moloney leukemia virus 10 (MOV10) (Zhang et al, 2016) also have been reported can interact with importin α to inhibit viral vRNP imported into nucleus. Therefore, aggregation of NP in mPSCs Oct4+ might block vRNP nuclear import, then interfere with vRNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability assay. Cell viability was determined by using the CellTiter-Glo kit (Promega, Madison, WI) as described previously (65,67). Briefly, A549 cells seeded in opaque-walled 96-well plates containing 100 or 10 M 4-CMTB or Cmp58 were cultured for 24 h, and A549 cells transfected with different siRNAs at a concentration of 30 nM were cultured for 48 h. CellTiter-Glo reagent (100 l) was then added directly into each well to induce cell lysis on a shaker for 10 min before luminescence was measured with a GloMax 96 microplate luminometer (Promega).…”
Section: Fig 10mentioning
confidence: 99%
“…The yeast two-hybrid screen to identify M1 interacting protein was performed as previously described (Luo et al, 2018). The yeast two-hybrid screen to identify M1 interacting protein was performed as previously described (Luo et al, 2018).…”
Section: Yeast Two-hybrid Assaymentioning
confidence: 99%
“…We used a Make Your Own "Mate&Plate™" Library System kit (Clontech) to construct the cDNA library from lung tissues of C57BL/6 mice. The yeast two-hybrid screen to identify M1 interacting protein was performed as previously described (Luo et al, 2018).…”
Section: Yeast Two-hybrid Assaymentioning
confidence: 99%